Bacterial ribosome collision sensing by a MutS DNA repair ATPase paralogue - Cerullo, Federico; Filbeck, Sebastian; Patil, Pratik Rajendra; Hung, Hao-Chih; Xu, Haifei; Vornberger, Julia; Hofer, Florian W.; Schmitt, Jaro; Kramer, Günter; Bukau, Bernd; Hofmann, Kay; Pfeffer, Stefan; et al. (Nature, 2022)
Ribosome stalling during translation is detrimental to cellular fitness, but how this is sensed and elicits recycling of ribosomal subunits and quality control of associated mRNA and incomplete nascent chains is poorly understood1,2. Here we uncover Bacillus subtilis MutS2, a member of the conserved MutS family of ATPases that function in DNA mismatch repair3, as an unexpected ribosome-binding protein with an essential function in translational quality control. Cryo-electron microscopy analysis of affinity-purified native complexes shows that MutS2 functions in sensing collisions between stalled and translating ribosomes and suggests how ribosome collisions can serve as platforms to deploy downstream processes: MutS2 has an RNA endonuclease small MutS-related (SMR) domain, as well as an ATPase/clamp domain that is properly positioned to promote ribosomal subunit dissociation, which is a requirement both for ribosome recycling and for initiation of ribosome-associated protein quality control (RQC). Accordingly, MutS2 promotes nascent chain modification with alanine-tail degrons - an early step in RQC - in an ATPase domain-dependent manner. The relevance of these observations is underscored by evidence of strong co-occurrence of MutS2 and RQC genes across bacterial phyla. Overall, the findings demonstrate a deeply conserved role for ribosome collisions in mounting a complex response to the interruption of translation within open reading frames.
Das PDF enthält einen Anhang von 24 Seiten
Gesehen am 17.03.2022